National Breeding System of Dairy Cattle Husbandry - Diwyanto, K; Anggraeni, Anneke (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 1999)
The husbandry of domestic dairy cattle as one of the components ofÂ livestock sub-sector development is hopefully to increase numerously the capacity and the quality on its milk production, to gradually meet national milk demand and face the competitiveness at the global. The achievement of this purpose should be supported by the production of dairy breeding stock in good quality and sufficient number to increase efficiency of both quantity and quality of domestic milk production. One of important aspect that should be prepared is in determining national breeding system of dairy cattle that can function effectively as guidance and regulation for producing, distributing, and using dairy cattle as âdomestic breeding stockâ. As in other livestock, breeding system of dairy cattle basically constituted of three main subsystems, i.e. production , distribution and marketing, and quality establishment subsystem. The paper discusses some aspects of these three subsystems to give considerable input in preparing the national concept of dairy cattle breeding system. enterprise (Animal Production 1(2): 43-55 (1999)Â KeyWords: dairy cattle, breeding stock, milk production.